Recurrent intussusception in an adult with variable appearances on CT scan and laparotomy findings - J., Masiyati; Ab. Hamid, Suzana; Abd Rahim, Ezamin; Bahari, Norafida; Mohamad Saini, Suraini (Community Health Society Malaysia, 2015)
Intussusception in adult is a rare and the management of this is still controversy. We report such a case of recurrent proximal small bowel intussusception in an adult which has variable appearances on Computed Tomography and laparotomy findings. Intussusception can recur again if underlying caused was not treated or removed. Surgical intervention with treatment or removal underlying cause of intussusception in adult is suggested to prevent recurrent of intussusception.